Penentuan Siswa Berprestasi Menggunakan Metode K-Nearest Neighbor dan Weighted Product (Studi Kasus : SMP Negeri 3 Mejayan) - Jodi Irjaya Kartika; Edy Santoso; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Education has an important role to develop this country. The school as an educational institution must develop a variety of guidance systems that are motivating and developing potential of the student. One of them with the selection of student achievement.However, the general election student achievement is more focused in academic achievement. As in JHS 3 Mejayan, has no balance in election of student achievement because in the process of selecting student achievement weight voting greater than the value of the non-academic. So there a rises of a problem in determining the best weighting of each criterion both of them and it really takes time to selection of student achievement. To make it come true, needs to be made for a system that able to work fast and objectively in decision making so that the result were correct and could be called as student achievement. In manufacturing of a system is necessary to suppor the methods used. The methods used are K-Nearest Neighbor as a classifier and Weighted Product as to sorting. Based on the comparison between data expert with manually calculation from the school and output data system for K-Nearest Neighbor's method has an accuracy continuesly 56.67 % and 76.67%. Then, ranked comparison between data expert with manually calculation from the school and output data system for Weighted Product's method has an accuracy continuesly 11,1 % and 100%.